On track - "Brown, Justin" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Mike designs a new transport station, builds a roller-coaster in a shopping mall, gets the library going and puts "cool" into "school."
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Children's short stories, New Zealand